205k views
23 votes
(05.05 LC)

If you were to use the substitution method to solve the following system, choose the new
equation after the expression equivalent to x from the second equation is substituted into
the first equation. (5 points)
3x + 2y = -21
x-3y=4
3(3y + 4) + 2y = -21
O 31-3y + 4) + 2y = -21
3x + 2(3y + 4) = -21
3x + 21-3y + 4) = -21

1 Answer

3 votes

Yes it is yep correct 1000% 10000000000000%

User Ram Sharma
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.